The Need-Relevant Instructor Behaviors Scale: Development and Initial Validation - Quested, Eleanor; Ntoumanis, Nikos; Stenling, A.; Thogersen-Ntoumani, Cecilie; Hancox, J. (Human Kinetics, 2018)
Purpose: This article outlines the development and validation of the Need-Relevant Instructor Behaviors Scale (NIBS). Drawing from self-determination theory, the NIBS is the first observation tool designed to code the frequency and the intensity of autonomy-, competence-, and relatedness-relevant behaviors of exercise instructors. The scale also captures the frequency of need-indifferent behaviors. Methods: The behaviors of 27 exercise instructors were coded by trained raters on two occasions, before and after they received training in adaptive motivational communication. Results: Findings supported the structural validity and reliability of the scale. The scale’s sensitivity to detect changes in frequency and intensity of need-relevant behaviors was also evidenced. Conclusions: The NIBS is a new tool that offers a unique, tripartite assessment of need-relevant behaviors of leaders in the physical activity domain.